2023
DOI: 10.3390/molecules28083475
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Remarkable Chemotherapeutic Potential of Polyphenolic Antioxidants in Battling Various Forms of Cancer

Abstract: Plant-derived compounds, specifically antioxidants, have played an important role in scavenging the free radicals present under diseased conditions. The persistent generation of free radicals in the body leads to inflammation and can result in even more severe diseases such as cancer. Notably, the antioxidant potential of various plant-derived compounds prevents and deregulates the formation of radicals by initiating their decomposition. There is a vast literature demonstrating antioxidant compounds’ anti-infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 123 publications
0
8
0
Order By: Relevance
“…Plant-derived compounds, particularly antioxidants, play a vital role in neutralizing free radicals present in various disease conditions. The sustained production of free radicals within the body can lead to inflammation and potentially more severe diseases, including cancer ( 39 ). Numerous studies have demonstrated the anti-inflammatory, anti-diabetic, and anti-cancer potential of antioxidant compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Plant-derived compounds, particularly antioxidants, play a vital role in neutralizing free radicals present in various disease conditions. The sustained production of free radicals within the body can lead to inflammation and potentially more severe diseases, including cancer ( 39 ). Numerous studies have demonstrated the anti-inflammatory, anti-diabetic, and anti-cancer potential of antioxidant compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Mohammad Imranet al have shown that kaempferol can be used in the form of chitosan nanoparticles, gold nanoclusters, and submicron emulsions, which allow it to achieve higher bioavailability and exert more pronounced inhibitory effects in tumor models. The study also showed that kaempferol can be used in the form of chitosan nanoparticles, gold nanoclusters, and submicron emulsions [ 91 ]. Carboxymethyl chitosan, which is carboxylated from chitosan, has good water solubility and biodegradability and is one of the best choices as a nanomaterial.…”
Section: New Technologies / Novel Drug Delivery Systemsmentioning
confidence: 99%
“…Most antitumor drugs have an immunosuppressive effect, which can reduce the body’s defense function and make the body susceptible to bacterial infections, and there are some reports that the combined use of anticancer and antibacterial drugs can reduce bacterial invasion of cancer patients. , Naringenin (the chemical structure in Scheme ) is a flavonoid from the flavonoid group of polyphenols that is widely found in a variety of herbs and fruits. It has lots of biological activities, with antioxidant, anti-inflammatory, and anticancer effects . Although naringenin has more pharmacological effects, its poor water solubility leads to poor absorption in the body.…”
Section: Introductionmentioning
confidence: 99%